STRATEGY OF RELIGIOUS MODERATION THROUGH INTERFAITH DIALOGUE AT THE CENTER FOR INTERDISCIPLINARY RELIGIOUS AND CULTURAL STUDIES (PSIAB) SEMARANG: STRATEGI MODERASI BERAGAMA MELALUI DIALOG LINTAS IMAN DI PUSAT STUDI INTERDISIPLINER AGAMA DAN BUDAYA (PSIAB) SEMARANG - Dini Rahmawati; Sibawaihi, Sibawaihi; Ichsan, Ichsan (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
Interfaith dialogue is one of the programs at the Center for Interdisciplinary Studies of Religion and Culture (PSIAB) Semarang, which in its activities involves participants with different faith backgrounds, this program aims to understand how to understand other religions and what their perspectives are, so that harmony is created between religious communities. The researcher used a qualitative approach with a case study method to explore the process of strengthening religious moderation through interfaith dialogue, then in data collection, data collection techniques were used which were carried out through in-depth interviews, participatory observation, and documentation studies. The results of the study showed that the interfaith dialogue activities organized by PSIAB made a real contribution to strengthening the religious moderation program initiated by the Ministry of Religion. Through thematic discussions and interfaith scripture studies, this activity encouraged participants to think critically and reflectively about differences in beliefs, while maintaining a balance between the steadfastness of personal faith and respect for diversity. Moderation in this case is understood as an inclusive and peaceful way of practicing religion. This study aims to emphasize the importance of an empirical approach in understanding religious moderation, by making dialogue practices at PSIAB a concrete example of openness-based education that strengthens social cohesion in a multi-cultural society through scriptural reasoning, thematic approaches, and curriculum integration.